Genomic signatures of habitat isolation and paleo-climate unveil the “island-like” pattern in the glasshouse plant Rheum nobile - Hum Kala Rana; Santosh Kumar Rana; Hang Sun; Dong Luo (Global Ecology and Conservation)
The Himalaya and the Hengduan Mountains, known for their ‘Sky Islands’ ecosystems, offer a unique opportunity to study genomic differentiation of endemic plants. While there is growing research on the genetic mechanisms underlying the distinctiveness of species in these regions, gaps remain in understanding the specific genomic processes shaping the “island-like” genetic structure of Rheum nobile. This study investigates R. nobile, a distinctive glasshouse plant native to the alpine-subnival belt, to uncover the genetic dynamics contributing to its “island-like” structure and genetic diversity in these unique ecosystems. We analyzed plastome and Internal Transcribed Spacer (ITS) sequences from 104 R. nobile samples, revealing significant genetic structure with significant unique alleles across populations. Three phylogroups were identified, corresponding to the floristic regionalization of the Himalaya and the Hengduan Mountains. The three main lineages diverged allopatrically around 7.38–4.19 million years ago (Mya). Notably, a significant population bottleneck occurred between 0.18–0.016 Mya (plastome) and 0.38–0.031 Mya (ITS). There was no correlation between genetic patterns and geographic or environmental distances. Gene flow was limited across three phylogroups. Ensemble Species Distribution Modelling suggested multiple refugia during or even before the Last Glacial Maximum, indicating a complex historical distribution. The “island-like” genetic patterns of Rheum nobile results from fragmented habitats and prolonged isolation during the Quaternary glaciation. This study highlights the species’ evolutionary trajectory shaped by ecological adaptation, and climatic fluctuations, providing valuable insights for future conservation and management efforts in its native environment.